LEPPIM Intensive Class (LIC): Student scientific essay writing training - Bening Cipta Alam; Eka Ariya Mutiara; Syifaul Fuada; Leonardi Paris Hasugian; Karynda Natalie Theofilus; Ashza Nur Siam; Mahmudah Salwa Gianti; Aan Yulianto; Ellis Susmawati (Universitas Muhammadiyah Magelang, 2023)
The LEPPIM Intensive Class (LIC) 2023 is an annual work program organized by the Department of Student Resource Development (DPSDM), serving as the first cadre level for new LEPPIM UPI Purwakarta 2023 students. The goal of the LEPPIM Intensive Class 2023 is to provide a comprehensive understanding of writing ethics and the scientific essay structure. The method employed involves creating a training concept through lectures featuring professional speakers. The level of student understanding is evaluated by comparing pre-test and post-test results, which are conducted using Google Forms. Upon comparing the pre-test and post-test results, it was observed that there was a 15.5% increase in participants' understanding of writing ethics and a 16.3% increase in their comprehension of the structure of scientific essays. Therefore, it can be concluded that this activity has successfully enhanced the participants' understanding of writing ethics and the structure of scientific essays.